The effect of different anaesthetic mask shapes on the anatomical dead space using infant, child and adult part-task trainers. (3rd September 2018) - Botes, L; Jacobs, J; Rademeyer, R; Van der Merwe, S; Van Heerden, L; Diedericks, BJS
Abstract : Dead space is the portion of tidal volume that does not participate in alveolar gas exchange. The purpose of this study was to compare the dead space contribution of differently shaped masks, of the same size, by measuring the volume of each mask. The study was conducted in the Clinical Simulation Unit of the School of Medicine, University of the Free State (UFS) using formed masks with inflatable polyvinylchloride (PVC) cuffs and rounded masks with non-inflatable PVC cuffs. The masks were placed on the faces of the infant, child and adult part-task trainers as well as on a flat surface. The cuffs of the formed masks were inflated to 5 cm water and 70 cm water. Masks were filled with water and the volume was measured. The volumes (ml) of the masks on the flat surface were significantly larger than those measured on the part-task trainers' faces. The volume of the rounded masks was greater than the volume of the formed masks. The amount of cuff inflation pressure (5 cm water vs. 70 cm water) did not lead to a significant change in mask volume: 102.3 ml (standard deviation [SD] 75.9) vs. 110.2 ml (SD 82.3), averaged for all sizes. Formed masks contribute less to anatomical dead space than rounded masks and are thus possibly the better choice. Cuff inflation pressure has insignificant influence on dead space volume.